Perkembangan Objek Wisata Religi Mesjid Agung Madani Islamic Center di Pasir Pengaraian, Kabupaten Rokan Hulu (2010-2017) - Diana Agustina; Siti Fatimah (PAMA Aksara, 2019)
This paper examines, why the Pasir Pangaraian Islamic Center Great Mosque became popular in 2015? Has the Pasir Pangaraian Islamic Center Great Mosque fulfilled the criteria as a religious tourist attraction? The method used is the historical method which is carried out through four stages, namely source collection (heuristics), source criticism, interpretation, and historiography. The results of this study indicate that, first, the development of the Great Mosque of the Islamic Center of Pasir Pangaraian from 2010 to 2017 has increased in terms of service. The construction of mosque infrastructure is getting better with the award received by the Great Mosque of the Islamic Center of Pasir Pangaraian as the best mosque in 2015. Secondly, the Great Mosque of Islamic Center Pasir Pangaraian can be said as one of the tourist objects because it meets several criteria as religious tourism, such as provide physical and spiritual freshness, as a place of prayer, dzikir and pray, as religious activities, as community activities. Third, the pattern of building and developing mosques so that the Great Mosque of the Islamic Center of Pasir Pangaraian became popular due to the role and cooperation carried out by the mosque administrators with the government, mosque administrators with the community, and administrators with the company.